POTENSI EKSTRAK ETANOL DAUN KAYU MANIS (Cinnamomum burmanii) TERHADAP PENURUNAN KADAR GLUKOSA DARAH DARI TIKUS PUTIH JANTAN (Rattus norvegicus) YANG DI INDUKSI SUKROSA - Kondoy, Sisko; Wullur, Adeanne; Bodhi, Widdhi (PHARMACON, 2013)
ABSTRACT Cinnamon leaf has been used traditionally for lowering glucose level. The objective of this research were to determine ethanolic extract of cinnamon leaf potention to lowering high glucose level to white male wistar induct by sucrose. Cinnamon leaf came from rain forest in Langowan, Minahasa. There are three categories of this leaf based of its leaf color, which is pale red, baby green, and dark green. The baby green leaf has been used to get the extract. Potention to lowering glucose level from extract compared by glibenclamide as positif control. Results of this research showed ethanolic extract with 5%, 10%, 20% b/v can inhibited Î±-glucosidase activity. Cinnamon leaf extract with concentration 20% can lowering glucose level until 101 mg/dl. This concentration gave higher affect than concentration 5% was 108 mg/dl and 10% was 105 mg/dl. Glucose level from white male wistar analyzed using enzimatik reaction with glucose test strip. The conclusion was ethanolic extract from cinnamon leaf can lowering glucose level from white male wistar induct by sucrose. Keywords : Cinnamon leaf, ethanolic extract, glucose level.